THE INFULENCE OF CREDIT RATING, ASSET TANGIBILITY, PROFITABILITY, LONG-TERM INVESTMENT, SHORT-TERM INVESTMENT ON CAPITAL STRUCTURE DECISION (Empirical Study on Non-Financial Company that listed on Indonesian Stock Exchange and registered in PEFINDO 2010- - Giovanni, Axel; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2015)
This study aimed to examine the effect of credit rating, asset tangibility, profitability, long-term investment, short-term investment on capital structure decision. Sample of this study used non-financial companies that listed on Indonesian Stock Exchange and registered on PEFINDO during 2010-2014. This research was made because there are differences in results between studies with each other.The sampling technique used in this research is purposive sampling method covering 15 companies as samples. The analysis used multiple regression, which is preceeded by a test consisting of the classical assumption test for normality, multicollinearity test, heteroscedasticity test and autocorrelation test. Hypothesis testing is using F test and t test.The result of this research show that credit rating and profitability had significant negative effect on capital structure decision as well as long-term investment variable had significant positive effect on capital structure decision. In addition, the results did not support that asset tangibility and short-term investment had significant effect on capital structure decision. Moreover it found that the value of the adjusted R square is 41.5%. This means that 58.5% is explained by other variables outside the model.Â